Microbiological characteristics of bacteremias among COVID-19 hospitalized patients in a tertiary referral hospital in Northern Greece during the second epidemic wave. (2nd December 2021) - Protonotariou, Efthymia; Mantzana, Paraskevi; Meletis, Georgios; Tychala, Areti; Kassomenaki, Angeliki; Vasilaki, Olga; Kagkalou, Georgia; Gkeka, Ioanna; Archonti, Maria; Kati, Styliani; Metallidis, Simeon; Skoura, Lemonia
ABSTRACT: Northern Greece was struck by an intense second COVID-19 (coronavirus disease 2019) epidemic wave during the fall of 2020. Because of the coinciding silent epidemic of multidrug-resistant organisms, the handling of COVID-19 patients became even more challenging. In the present study, the microbiological characteristics of bacteremias in confirmed cases of hospitalized COVID-19 patients were determined. Data from 1165 patients hospitalized between September and December 2020 were reviewed regarding the frequency of bloodstream infections, the epidemiology and the antibiotic susceptibility profiles of the causative bacteria. The hospital's antibiotic susceptibility data for all major nosocomial pathogens isolated from bacteremias of COVID-19 patients between September and December 2020 versus those between September and December 2019 were also compared. Overall, 122 patients developed bacteremia (10.47%). The average of time interval between hospitalization date and development of bacteremia was 13.98 days. Admission to ICU occurred in 98 out of 122 patients with an average stay time of 15.85 days and 90.81% in-hospital mortality. In total, 166 pathogens were recovered including 114 Gram-negative bacteria and 52 Gram-positive cocci. Acinetobacter baumannii was the most frequent ( n = 51) followed by Klebsiella pneumoniae ( n = 45) and Enterococcus faecium ( n = 31). Bacteremias in hospitalized COVID-19 patients were related with prolonged time of hospitalization and higher in-hospital mortality, and the isolated microorganisms represented the bacterial species that were present in our hospital before the COVID-19 pandemic. Worryingly, the antibiotic resistance rates were increased compared with the pre-pandemic era for all major opportunistic bacterial pathogens. The pandemic highlighted the need for continuous surveillance of patients with prolonged hospitalization. Abstract : COVID-19 patient bacteremias in a Greek referral hospital.